The radius of the circle having centre at (2,1) whose one chord is the diameter of the circle x2 +y2 -2x-6y+6=0

2 years ago

Share

Answers : (1)

                                        

x2+y2-2x-6y+6=0


or, (x2-2x+1)+(y2-6y+9)-4=0


or, (x-1)2+(y-3)2=22


thus the radius of the smaller given circle is 2 and its centre is (1,3).


distance b/w the two centres = (1+4)1/2 = 51/2


thus the radius of required circle = (5 + 4)1/2 = 3.

2 years ago

Post Your Answer

More Questions On Analytical Geometry

Ask Experts

Have any Question? Ask Experts
Post Question
 
Answer ‘n’ Earn
Attractive Gift
Vouchers
To Win!!!
Click Here for details
If the vertices of triangles are placed at (0,0), (0,6), (6,0). The prove that the distance between the orthocentre and circumcentre is 3 root2.
 
 
Solution: As we know the.. orthocentre is the point of intersection of altitudes of the triangle... soo for right angle triangle.. orthocenter is the vertex itself on which right angle is...
  img
Ajay Verma 2 months ago
A straight line through p(2,3) inclined at an angle 60 degrees with positive y axis in clockwise direction.The co-ordinates of one of the points on it at a distance 4 units from P is.?
 
 
solution: as shown.. the equn of the line (x – x 1 ) / cos A = ( y – y 1 ) / sin A = R where A = angle of inclination with X-axis R = distance of the point on the line so ( x...
  img
Ajay Verma 2 months ago
prove that four straight lines represented by the equation 12x 2 +7xy -12y 2 =0 and 12x 2 +7xy -12y 2 -x +7y -10 form a square
 
 
Hello Student, 12x2+7xy -12y2=0 12x2+7xy -12y2-x +7y -10 with first x=(-7y +- yroot(49+144*4))/24 you will get 2 lines from here with second do the same thing x=(-7y+1 +- root((7y-1)^2...
  img
Arun Kumar 3 months ago
find dy/dx when y= e^(3x) sin 4x . 2^x
 
 
Hello Student, Thanks & Regards Arun Kumar Btech, IIT Delhi Askiitians Faculty
  img
Arun Kumar 2 months ago
If a+b=c, prove that cos^2 a+cos^2b+cos^2c =1+2cosacosbcosc
 
 
cos^2a +cos^2b+cos^2c= (1+cos2a)/2+(1+cos2b)/2+cos^2c =1+(1/2)*(2cos(a+b)cos(a-b) +cos^2c (since a+b+c = 0) =1 + cos(-c)cos(a-b)+cos^2c (since cos(-a) = cosa) =1+cos(c)cos(a-b)+cos^2c...
 
Y RAJYALAKSHMI 2 months ago
Rationalise denominator 1/2+√3.
 
 
Hello Student, Thanks & Regards Arun Kumar Btech, IIT Delhi Askiitians Faculty
  img
Arun Kumar 2 months ago
View all Questions »